The Urgency of Enacting Asset Forfeiture Legislation in Relation to Criminal Offenses: A Perspective of Justice and Utility - Muhammad Lutfi Pratama; Rasji Rasji (Universitas Islam Sultan Agung, 2025)
Along with the times, economic crimes are increasingly massive and structured. The complexity of these criminal acts can be seen from the development of modes used in carrying out crimes, such as the ease of escaping money from criminal acts which only takes a short time. The construction of the legal system, which currently focuses only on the confiscation of assets through criminal proceedings, is often limited in effectiveness because it requires a court decision with permanent legal force. This causes many assets resulting from crime that cannot be used for the benefit of the state or society. As a form of parliamentary support, the idea emerged to regulate the confiscation of assets resulting from criminal acts in a special law. However, the ratification of the Asset Forfeiture Bill has not been carried out until the time this research is written. This condition reflects the existence of obstacles in the legislation process that have an impact on efforts to eradicate crimes, especially in terms of the confiscation of assets resulting from crime. There are two main problems that will be raised, the first is how the practice of confiscating assets resulting from criminal acts in Indonesia according to the applicable rules is reviewed from the perspective of justice and utility. Second, how is the urgency of the Law on Asset Forfeiture Related to Criminal Acts reviewed through the perspective of justice and benefits. The type of research used is normative legal research. The nature of the research used is Descriptive Legal Research with the type of data used is secondary data. The data collection technique is carried out by library research through a statute approach and a conceptual approach.